The Change in Environmental Variables Linked to Climate Change Has a Stronger Effect on Aboveground Net Primary Productivity Than Does Phenological Change in Alpine Grasslands - Wang, Jiangwei; Li, Meng; Yu, Chengqun; Fu, Gang (Frontiers in Plant Science, 2022)
More and more studies have focused on responses of ecosystem carbon cycling to climate change and phenological change, and aboveground net primary productivity (ANPP) is a primary component of global carbon cycling. However, it remains unclear which one of climate change and phenological change on ANPP is stronger. In this study, we compared the effects of phenological change and climate change on ANPP during 2000–2013 across 36 alpine grassland sites on the Tibetan Plateau. Our results indicated that ANPP showed a positive relationship with plant phenology such as prolonged length of growing season and advanced start of growing season, and environmental variables such as growing season precipitation (GSP), actual vapor pressure (Ea), relative humidity (RH) and the ratio of GSP to ≥5 oC accumulated temperature (GSP/AccT), respectively. The linear change trend of ANPP increased with that of GSP, Ea, RH and GSP/AccT rather than phenology variables. Interestingly, GSP had the closer correlation with ANPP and meanwhile the linear slope of GSP had the closer correlation with that of ANPP among all the concerned variables. Therefore, climate change, mainly attributed to precipitation change, had stronger effects on ANPP than did phenological change in alpine grasslands on the Tibetan Plateau.